Autologous hematopoietic stem cell transplantation experience in patients with diffuse cutaneous systemic scleroderma - Bazán-Ruiz, Susy (2021)
Background: The progression and lack of therapeutic options leads to a large increase in morbidity and mortality in diffuse cutaneous systemic scleroderma. Clinical Case: Three patients with a diagnosis of rapidly progressing systemic scleroderma without severe cardiopulmonary or renal involvement with multiple lines of treatment including high doses of cyclophosphamide, submitted to autologous transplant (2015-2020) with conditioning based on Cyclophosphamide and Antithymocyte Globulin are presented as a therapeutic option. During the procedure, no various infectious infections were observed with a medullary seizure on day 10 and an average relapse of 9.6 months. Conclusions: Due to the good toxicity profile and good tolerance to the procedure, Autologous Transplantation should be considered as a treatment option in patients without high accumulated doses of cyclophosphamide or in early stages of disease.